Hybrid Lipid/Clay Carrier Systems Containing Annatto Oil for Topical Formulations - Raquel de Melo Barbosa; Aliana Monteiro Leite; Fátima García-Villén; Rita Sánchez-Espejo; Pilar Cerezo; César Viseras; Angela Faccendini; Giuseppina Sandri; Fernanda Nervo Raffin; Túlio Flávio Accioly de Lima e Moura (MDPI AG, 2022)
Nanocomposites formed by clay and lipid carriers (NLCs) show a high potential for providing controlled release and specific delivery of bioactive molecules and have recently gained attention in the pharmaceutical sector due to their ability to transport hydrophilic and hydrophobic drugs. Recent studies have recognized the biological activity of the oil of Bixa orellana L. (AO) with regards to its healing, antioxidant, antibacterial, and anti-leishmanial properties. Therefore, the purpose of this study is the preparation and characterization of hybrid systems based on lipid nanocarriers and laponite for the delivery of AO. NLCs were prepared by the fusion-emulsification method, using cetyl palmitate (CP) or myristyl myristate (MM), AO, and Poloxamer 188. The morphology, hydrodynamic diameters, zeta potential (ZP), polydispersity index (PDI), thermal analysis, X-ray diffraction analysis (XRD), viscosity behavior, and cytotoxicity testing of the hybrid systems were performed. The thermal study and X-ray diffraction analyses (XRD) revealed polymorphic structural changes compatible with the amorphization of the material. Rheological assays highlighted a typical pseudoplastic behavior in all systems (MM and CP with LAP). The hybrid systems' morphology, size diameters, and PDIs were similar, preset spherical and monodisperse structures (≈200 nm; <0.3), without significant change up to sixty days. The ZP values differed from each other, becoming higher with increasing AO concentration. XEDS spectra and elemental X-ray maps show peaks of lipids (organic components, C and O) and inorganic components O, Mg, and Si. All samples showed cell viability above 60%. The results indicated a stable, biocompatible hybrid system that can be an alternative for topical application.